Serotonin type 3 receptor subunit gene polymorphisms associated with psychosomatic symptoms in irritable bowel syndrome: a multicenter retrospective study - Berens, Sabrina; Dong, Yuanjun; Fritz, Nikola; Walstab, Jutta; D'Amato, Mauro; Zheng, Tenghao; Wahl, Verena; Boekstegers, Felix; Lorenzo Bermejo, Justo; Martinez, Cristina; Mellein, Stefanie; Clevers, Egbert; et al. (World journal of gastroenterology, 2022)
Serotonin type 3 receptor subunit gene polymorphisms associated with psychosomatic symptoms in irritable bowel syndrome: A multicenter retrospective study
Gesehen am 05.07.2022